Formação para o sus: uma análise sobre as concepções e práticas pedagógicas em saúde coletiva - Damiance, Patrícia Ribeiro Mattar; Tonete, Vera Lúcia Pamplona; Daibem, Ana Maria Lombardi; Ferreira, Maria De Lourdes Da Silva Marques; Bastos, José Roberto De Magalhães (Fundação Oswaldo Cruz, Escola Politécnica de Saúde Joaquim Venâncio, 2016)
Abstract The pedagogical preparation of educators in the health area, in the face of the demands of contemporary education and of the Brazilian curriculum guidelines, is directly related to the training of professionals to meet the needs of the Unified Health System. Based on this premise, this study investigates the training profile, the bases of the action, and the pedagogical planning of the professor of nursing who is the advisor of the internship in Collective Health at colleges in two mid-western municipalities in the state of São Paulo, Brazil, under the light of the public policies of education and health. The data obtained were submitted to thematic content analysis. The analysis showed that the pedagogical practice of the 11 professors surveyed was influenced by the institutional culture of Brazilian higher education. Routine activities were modeled based on biological science contents, organized under the aegis of nursing care; on oral and reproductive biomedical techniques; on the disarticulation between theory and practice, and on the isolation of teaching. It was concluded that the teaching skills in the educational, organizational, and relational dimensions need to be enhanced towards the planning of pedagogical action, approaching the theoretical and philosophical references of the UHS and contemporary education, seeking an integrated, collective, democratic, and practice promoting health and quality of life.

Resumen La preparación pedagógica del docente del área de la salud, frente a las exigencias de la educación contemporánea y las directrices curriculares nacionales, guarda una relación directa con la formación de profesionales para atender las necesidades del Sistema Único de Salud. Fundamentado en esa premisa, este estudio buscó analizar perfil de formación, bases de la acción y planificación pedagógica del docente de enfermería orientador de la pasantía en Salud Colectiva de instituciones de enseñanza superior de dos municipios de la región centro oeste del estado de San Pablo, Brasil, a la luz de las políticas públicas de educación y salud. Los datos obtenidos se sometieron a análisis de contenido, modalidad temática. El análisis llevado a cabo señaló que la práctica pedagógica de los 11 docentes entrevistados presentaba influencia de la cultura institucional de la educación superior brasileña. Las actividades rutinarias estaban inspiradas en contenidos de las ciencias biológicas, organizados en torno a la asistencia de enfermería; en la exposición oral y reproducción de técnicas biomédicas; en la desarticulación entre teoría y práctica y en el aislamiento del trabajo docente. Se concluyó que las competencias docentes en las dimensiones educativas, organizacionales y relacionales deben ser ampliadas en dirección a la planificación de la acción pedagógica, aproximándose a las referencias teóricas y filosóficas del SUS y de la educación contemporánea, en busca de una práctica integrada, colectiva, democrática, promotora de la salud y la calidad de vida.

Resumo O preparo pedagógico do docente da área da saúde, diante das exigências da educação contemporânea e das diretrizes curriculares nacionais, tem relação direta com a formação de profissionais para atender às necessidades do Sistema Único de Saúde. Fundamentado nessa premissa, este estudo buscou analisar perfil de formação, bases da ação e planejamento pedagógico do docente de enfermagem orientador de estágio em Saúde Coletiva de instituições de ensino superior de dois municípios do centro-oeste paulista, à luz das políticas públicas de educação e saúde. Os dados obtidos foram submetidos à análise de conteúdo, modalidade temática. A análise empreendida apontou que a prática pedagógica dos 11 docentes entrevistados sofria influência da cultura institucional da educação superior brasileira. As atividades rotineiras estavam calcadas em conteúdos das ciências biológicas, organizados sob a égide da assistência de enfermagem; na exposição oral e reprodução de técnicas biomédicas; na desarticulação entre teoria e prática e no isolamento do trabalho docente. Concluiu-se que as competências docentes nas dimensões educacionais, organizacionais e relacionais precisam ser ampliadas em direção ao planejamento da ação pedagógica, aproximando-se dos referenciais teóricos e filosóficos do SUS e da educação contemporânea, em busca de uma prática integrada, coletiva, democrática, promotora da saúde e da qualidade de vida.
Training for the uhs: an analysis of the pedagogical conceptions and practices in public health
Formación para el sus: un análisis sobre las concepciones y prácticas pedagógicas en salud colectiva
Keywords: Education; teaching; Public Health; Unified Health System; clinical internship; educação; ensino; Saúde Coletiva; Sistema Único de Saúde; estágio clínico